OCULAR TRAUMA: A LITERATURE REVIEW OF CLASSIFICATION, EPIDEMIOLOGY, AND MANAGEMENT - Małgorzata Zach; Joanna Kłosowska; Karolina Błądzińska; Maciej Błądziński; Piotr Świerczek; Paula Folta; Dominika Machała; Kamila Machała; Anna Opalińska; Cezary Lubas (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Ocular trauma is a major global cause of visual impairment, accounting for an estimated 1.6 million cases of blindness annually. It presents significant clinical and socioeconomic challenges. This review provides an overview of the classification, epidemiology, causes, prevention and management of ocular trauma. State of knowledge: Eye injuries are broadly categorized into open-globe and closed-globe injuries, with further classification based on mechanism, anatomical zone and visual acuity. The Ocular Trauma Score (OTS) is a commonly employed prognostic tool, although its predictive accuracy has limitations. Ocular trauma disproportionately affects men and working-age individuals. Occupational and sports-related injuries are highly prevalent, and up to 90% are considered preventable with use of personal protective equipment. Prompt diagnosis and tailored management, including immediate irrigation for chemical injuries and urgent surgical intervention for open-globe trauma, are essential for optimal visual outcomes. Conclusions: Effective management of eye injuries relies on accurate classification and timely intervention. Standardized tools and education can improve outcomes, while public health efforts must prioritize prevention and access to care to reduce the global burden of ocular trauma. Materials and methods: A review of literature was conducted using Google Scholar and PubMed databases, focusing on articles published between 2020 and 2025.